Device electronics for integrated circuits - Muller, Richard S. (John Wiley & Sons, 1986)
This edition provides the required information for a course in modern device electronics taken by undergraduate electrical engineers. It offers major new coverage of silicon technology, adds several topics in basic semiconductor physics not treated previously, and introduces Hall-effect sensors. The chapters on MOSFET have been updated, focusing on mobility variations and threshold-voltage dependence. Additional topics include VLSI devices, short channel effects and computer modelling.